The existence of customary law and culture in law Pattinjo in the Millennial period - Sulaeman Sulaeman (Indonesia Prime, 2018)
Culture is one of the aspects that play a part in public life. IE can be wealth for each region. But culture is also very vulnerable to influences from the outside and will also influence the rapidly increasing technology, whether it be a positive or negative influence. Your own culture can rise, and fall can reduced, or berAdd all depends on human beings or a society that is concerned culture itself whether the man can bring about a change or an improvement on culture or even reduce or Even eradicate the culture